2019
DOI: 10.1049/iet-esi.2018.0047
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated operation strategies for natural gas and power systems in presence of gas‐related flexibilities

Abstract: A detailed investigation of the interaction between natural gas and power systems is necessary, due to the increasing interdependency of these vectors, especially in the context of renewable generations integration growth into the grid. In this study, an outer approximation with an equality relaxation decomposition method is proposed to solve a mixed-integer non-linear problem representing the operation of coupled natural gas and power systems. The proposed coupled modelling of natural gas and power systems is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…The constraints governing the electricity system over the time horizon (t ∈ T ) are represented by equations (1)-(11). These constraints include: minimum and maximum power generation limits for generators (1), Minimum Stable Generation (MSG) for thermal generators (2), maximum limit for power generation and provision of reserve by thermal generators (3), Minimum Up/Down Time (MUT/MDT) of generators (4)-(5), ramp up/down limits of generators (6), start-up cost of generators (7) (8), minimum reserve requirement (including the unserved reserve) (9) (Ameli et al, 2019), capacity of power transmission lines (10), and power balance at each time step (11).…”
Section: Formulation Of Electricity System Operationmentioning
confidence: 99%
See 1 more Smart Citation
“…The constraints governing the electricity system over the time horizon (t ∈ T ) are represented by equations (1)-(11). These constraints include: minimum and maximum power generation limits for generators (1), Minimum Stable Generation (MSG) for thermal generators (2), maximum limit for power generation and provision of reserve by thermal generators (3), Minimum Up/Down Time (MUT/MDT) of generators (4)-(5), ramp up/down limits of generators (6), start-up cost of generators (7) (8), minimum reserve requirement (including the unserved reserve) (9) (Ameli et al, 2019), capacity of power transmission lines (10), and power balance at each time step (11).…”
Section: Formulation Of Electricity System Operationmentioning
confidence: 99%
“…The operation of the gas system over the time horizon (t ∈ T ) is modeled via constraints for gas flow along a pipe (12) (Osiadacz, 1987) (detailed formulation is presented in Ameli et al, 2019), power consumption by the compressors 14, changes in the gas system linepack (15), minimum and maximum pressure limits (16), and gas balance at each node and time step (17). In order to model a bi-directional gas flow, in the gas flow equation in (12), the term Q…”
Section: Formulation Of Gas System Operationmentioning
confidence: 99%
“…Furthermore, gas compressors driven by electricity as well as the emergence of power to gas (Pegs) technology, increases the interdependency of gas and electricity systems [2]. Therefore, as this interaction between the electricity and natural gas infrastructures increases, operation of each network will impact the other energy vector, which emphasizes the importance of coordinated operation of ENGN from operation [3]- [5] and planning perspectives [6].…”
Section: A Motivation and Backgroundmentioning
confidence: 99%
“…In [5], the iterative and integrated operation models are compared, and it is shown that under completely identical conditions, the integrated method results in about 7% cost savings. It is also shown that the cost difference could be reduced by using flexible elements such as multi-directional compressors or flexible GFUs.…”
Section: B Relevant Literaturementioning
confidence: 99%
See 1 more Smart Citation